HUBUNGAN STATUS GIZI DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI DI DESA KEPENUHAN HULU - Rahmi Fitria; Duma Febryanty; Heny Sepduwiana; Siti Nurkhasanah (Jannatul Makwa Health : Jurnal Ilmiah Kesehatan (Scientific Journal of Health), 2024)
There are three nutritional problems for adolescents in Indonesia, namely malnutrition (stunting), micronutrient deficiencies that cause anemia, and overweight (obesity). Overweight is a condition in which a person's weight exceeds normal, while obesity is a condition of excess body fat accumulation, so that a person's weight is far above normal and can endanger health. Overweight and obesity occur due to an imbalance between incoming and outgoing energy, resulting in an increase in the ratio of fat and lean body tissue which is localized or evenly distributed throughout the body. Another problem is micronutrients, one of which is iron deficiency which is called anemia. Based on the results of the data, there will be 100 young women in Kepenuhan Hulu Village in 2023. The purpose of this study was to determine the relationship between nutritional status and the incidence of anemia in young women in Kepenuhan Hulu Village. This research methodology uses a cross sectional design. The population in this study amounted to 100 young women and the sample in the study was 80 young women who were in the Kepenuhan Hulu Village. The sample selection technique uses Simple Random Sampling. The average distribution of BMI for young women is 26.08 with an SD of 7.75. Data were analyzed using the T-Independent test to determine whether there was a relationship between nutritional status and the incidence of anemia. The results showed that there was a relationship between nutritional status and the incidence of anemia in young women with a p-value (Sig) of 0.000, which means that the p-value was <0.05. So it can be concluded that there is a significant relationship between nutritional status and the incidence of anemia. Suggestions need to be carried out in collaboration between schools, health centers, health agencies by carrying out health promotion about the importance of maintaining nutritional status and the dangers of anemia in young women. Keywords : Nutritional Status, Anemia, Young Girls